2008
DOI: 10.1017/s1368980007000262
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and associated lifestyle behaviours in Iran: findings from the First National Non-communicable Disease Risk Factor Surveillance Survey

Abstract: Objective: To assess the national prevalence of overweight and obesity, as well as some associated lifestyle behaviours, for the first time in Iran. Design and Settings: This population-based study was performed in early 2005 as part of the World Health Organization (WHO) STEPwise approach to noncommunicable diseases' risk factor surveillance. Dietary and physical activity habits were assessed by WHO questionnaires. Subjects: The study population comprised 89 532 subjects aged over 15 years living in the 28 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 21 publications
14
90
0
1
Order By: Relevance
“…The prevalence of obesity and overweight reported in Iran 3 18.1% and 32.0%, respectively. In another study 4 , overweight, obesity and pathologic obesity have been shown 28.6%, 10.8% and 3.4% of in adult people. The prevalence and pattern of obesity vary substantially from a nation to a nation, and its current prevalence (BMI ≥30 kg/m 2 ) ranges from as low as ≤ 5% in China, Japan, and African nations to as high as ≥75% in urban Samoa.…”
Section: Bangladesh Med Res Counc Bull 2010; 36: 100-103 Letters To Tmentioning
confidence: 85%
See 1 more Smart Citation
“…The prevalence of obesity and overweight reported in Iran 3 18.1% and 32.0%, respectively. In another study 4 , overweight, obesity and pathologic obesity have been shown 28.6%, 10.8% and 3.4% of in adult people. The prevalence and pattern of obesity vary substantially from a nation to a nation, and its current prevalence (BMI ≥30 kg/m 2 ) ranges from as low as ≤ 5% in China, Japan, and African nations to as high as ≥75% in urban Samoa.…”
Section: Bangladesh Med Res Counc Bull 2010; 36: 100-103 Letters To Tmentioning
confidence: 85%
“…More prevalence of obesity in women than men 4,8 and in urban area than rural area 2,3 has been shown in some studies. In the developing countries, migration started from rural to urban areas, and it led to lifestyle changes in recent decades.…”
Section: Bangladesh Med Res Counc Bull 2010; 36: 100-103 Letters To Tmentioning
confidence: 93%
“…5 As one of these countries, Iran has experienced both a rapid epidemiologic transition and change in the health and disease profile from predominantly infectious diseases to chronic non-communicable diseases. 6 Several cross-sectional studies have documented alarming prevalence rates of CVDs and their risk factors among the Iranian population, [7][8][9][10][11][12] but there is very limited data from longitudinal studies and those are limited to a metropolitan area of the capital city. 13 The Isfahan Cohort Study (ICS) is the first study of its kind, not only in Iran, but also in the Eastern Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%
“…16 Low physical activity and consumption of diet with more of carbohydrates and saturated fatty acids such as fast-food have been associated with hyperlipidemia. 17 According to Dancy habitually active men and women are less likely to have hyper triglycerides and less HDL concentration. The positive correlation between lipid profile and BMI, and HT were in collaboration with previous studies and reaffirmed the role of lipids in the pathophysiology of overweight and obesity as well as increased accumulation of lipids with age.…”
Section: Discussionmentioning
confidence: 99%